2021
DOI: 10.1212/con.0000000000000992
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Manifestations of Severe Acute Respiratory Syndrome Coronavirus 2 Infection

Abstract: PURPOSE OF REVIEW: This article describes the spectrum of neurologic complications associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, their underlying pathology and pathogenic mechanisms, gaps in knowledge, and current therapeutic strategies.RECENT FINDINGS: COVID-19 is the clinical syndrome caused by the novel coronavirus SARS-CoV-2. It can affect the entire neuraxis, and presentations in the acute phase are variable, although anosmia is a common manifestation. Encephalopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 84 publications
0
24
0
Order By: Relevance
“…Necropsic studies have proven some neuroinvasive capacity of SARS-CoV-2 7 , 10 , 11 . This virus may enter the brain through three potential mechanisms: transsynaptic spread from the olfactory bulb following intranasal exposure, migration across the BBB through endothelial cell infection, and migration following disruption of the BBB from resulting inflammation 12 14 . Pathologic studies have found a high prevalence of SARS-CoV2 RNA and surface protein structures in olfactory mucosa 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Necropsic studies have proven some neuroinvasive capacity of SARS-CoV-2 7 , 10 , 11 . This virus may enter the brain through three potential mechanisms: transsynaptic spread from the olfactory bulb following intranasal exposure, migration across the BBB through endothelial cell infection, and migration following disruption of the BBB from resulting inflammation 12 14 . Pathologic studies have found a high prevalence of SARS-CoV2 RNA and surface protein structures in olfactory mucosa 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic, several neurologic complications have been described, both as parainfectious (e.g., stroke, viral encephalitis) and postinfectious (e.g., myelitis) phenomena [ 1 ]. In addition, neuromuscular complications in close temporal relation with coronavirus disease-2019 (COVID-19) have been reported, the most frequent being Guillain-Barré syndrome (GBS) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 It is essential to recognize neurological involvement in COVID‐19, some of which require urgent intervention. 1 Transverse myelitis (TM) is one of the possible disorders associated with COVID‐19, with few cases described in the literature. 1 , 2 , 3 , 4 However, like other causes of spinal cord injury (SCI), management of complications must not be disregarded.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Transverse myelitis (TM) is one of the possible disorders associated with COVID‐19, with few cases described in the literature. 1 , 2 , 3 , 4 However, like other causes of spinal cord injury (SCI), management of complications must not be disregarded. Most case reports do not include the rehabilitation and the reality of the process after hospital discharge.…”
Section: Introductionmentioning
confidence: 99%